Perbuatan Melawan Hukum atas Penguasaan Hak Milik Tanah pada Sertifikat Ganda - Puji Rahmawati; Syafira Rahmania Arbi; Mohammad Nuralify (CV Rewang Rencang, 2025)
The issuance of duplicate land ownership certificates gives rise to legal issues that culminate in civil disputes between parties holding certificates over the same plot of land. These problems are not only caused by the involved parties but also by the negligence of land registration officials. This study aims to identify the forms of unlawful acts in cases of land control based on duplicate certificates, as well as to examine the mechanisms for resolving land ownership disputes in such cases in Indonesia. The research method employed is normative juridical, using data collection techniques based on statutory and conceptual approaches. The results of the study indicate that an unlawful act occurs when a person takes control of land that is legally owned by another party, whether an individual or a legal entity. Proof of lawful land ownership is essential to ensure legal certainty, which can be demonstrated through authentic deeds such as a Sale and Purchase Deed (Akta Jual Beli or AJB) issued by a Land Deed Official (Pejabat Pembuat Akta Tanah or PPAT). To minimize disputes, firm law enforcement is required, along with the active role of the National Land Agency (Badan Pertanahan Nasional or BPN) in resolving disputes fairly through deliberation, mediation, and facilitation. In practice, land dispute resolution is not only carried out by the BPN but can also be pursued through the General Courts and the Administrative Court